A new species of Carychium O.F. Müller, 1773 from Pakistan (Gastropoda: Carychiidae). (3rd July 2022) - Auffenberg, Kurt; Páll-Gergely, Barna
ABSTRACT: A new species of land snail, Carychium jochumae n. sp., is described from northern Pakistan, representing a new country record for the genus. The new species is compared to the nominal species occurring on the Indian subcontinent: Carychium indicum Benson, 1849, C. boysianum Benson, 1864, C. khasiacum Godwin-Austen, 1876, and C. parietidentatum (Das & Aravind, 2021), which are briefly discussed. urn:lsid:zoobank.org:pub:42EDF7BD-6C22-4918-B4F7-DFB0BF85A8FA